Efficacy of local therapy for oligoprogressive disease after programmed cell death 1 blockade in advanced non‐small cell lung cancer. Issue 12 (31st October 2020) - Kagawa, Yusuke; Furuta, Hiromi; Uemura, Takehiro; Watanabe, Naohiro; Shimizu, Junichi; Horio, Yoshitsugu; Kuroda, Hiroaki; Inaba, Yoshitaka; Kodaira, Takeshi; Masago, Katsuhiro; Fujita, Shiro; Niimi, Akio; et al.
Abstract: Immune checkpoint inhibitors (ICIs) have dramatically changed the strategy used to treat patients with non‐small‐cell lung cancer (NSCLC); however, the vast majority of patients eventually develop progressive disease (PD) and acquire resistance to ICIs. Some patients experience oligoprogressive disease. Few retrospective studies have evaluated clinical efficacy in patients with oligometastatic progression who received local therapy after ICI treatment. We conducted a retrospective analysis of advanced NSCLC patients who received PD‐1 inhibitor monotherapy with nivolumab or pembrolizumab to evaluate the effects of ICIs on the patterns of progression and the efficacy of local therapy for oligoprogressive disease. Of the 307 patients treated with ICIs, 148 were evaluated in our study; 42 were treated with pembrolizumab, and 106 were treated with nivolumab. Thirty‐eight patients showed oligoprogression. Male sex, a lack of driver mutations, and smoking history were significantly correlated with the risk of oligoprogression. Primary lesions were most frequently detected at oligoprogression sites (15 patients), and 6 patients experienced abdominal lymph node (LN) oligoprogression. Four patients showed evidence of new abdominal LN oligometastases. There was no significant difference in overall survival (OS) between the local therapy group and the switch therapy group (reached vs. not reached, P  = .456). We summarized clinical data on the response of oligoprogressive NSCLC to ICI therapy. The results may help to elucidate the causes of ICI resistance and indicate that the use of local therapy as the initial treatment in this setting is feasible treatment option. Abstract : This study showed the efficacy of local therapy for oligoprogressive disease after PD‐1 blockade in advanced non‐small‐cell lung cancer.